ANALISIS KEANDALAN (RELIABILITY) PADA MESIN SCREW PRESS (STUDI KASUS : PT. PERKEBUNAN NUSANTARA XIII) - Shiddiq Kurniawan; Qomariyatus Sholihah (Universitas Lambung Mangkurat, 2019)
The machine is one of the main factors of production whose role is very important in order to produce a product that conforms to the specifications set by a machine, with the amount and capacity of the machine's production. Reliability is the design of a component so that components can work according to function, without any failure, in accordance with the process already set. Screw press is a fitting machine used to squeeze moss brondolan ripe with press system and used to separate crude oil from crushed flesh (mesocarp) by squeezing. Research done on Screw Press machine that its role is quite high in PT. Perkebunan Nusantara XIII. The method used is Reliability with MTTR Method. From the calculation results obtained reliability value Screw Press engine in 2015 has the highest reliability value of 1.6408 at the time of calculation of 383.75 hours and in 2016 has a reliability value of 0.7239 at the time of calculation 415.83 hours. Screw Press engine reliability value in 2016 is higher than 2015, it is proven that the life of Screw Press engine in 2016 is more dominant than in 2015. The higher the reliability value the better the machine used in the operation process. Keywords : Reliability, Weibull, MTTR, Machine Screw Prees